Modeling Intra-Individual changes in Children's Social Skills at Home and at School: A Multivariate Latent Growth Approach to Understanding between-Settings Differences in Children's Social Skills Development - CHAN, David (Institutional Knowledge at Singapore Management University, 2000)
Multivariate latent growth modeling was used to conceptualize and analyze intraindividual changes in children's social skills and interindividual differences in these changes in home and school settings. Parent and teacher ratings assessing children's social skills at home and school settings, respectively, were obtained for a sample of 378 children at 4 time points spaced at approximately 12-month intervals over a 4-year period from Kindergarten to Grade 3. Results showed that, in initial status at Kindergarten, there were significant individual differences in social skills in both home and school settings and a significant positive association between initial status in social skills in the two settings. Systematic between-settings differences in children's social skill development were found. Social skills development at home was best described with a nonlinear trajectory in which skills increased from Kindergarten to Grade 2 with a substantially larger increase from Grade 1 to Grade 2 than from Kindergarten to Grade 1, and then remained relatively constant from Grade 2 to Grade 3. In contrast, social skills development at school was best described with a negative linear trajectory in which skills decreased at a constant rate from Kindergarten to Grade 3. The differences in social skills development may derive form the fact that different teachers with different expectations regarding social skills provided ratings each year while the same parent was the source of at-home social skills ratings. There were significant individual differences in growth rates in the school as well as the home setting. Evidence of between-settings differences in social skills development were obtained from differential patterns of associations between growth parameters (initial status and growth rate) and individual predictors (family income, parent education, child verbal skills) across settings.